B-Chronic Lymphocytic Leukemia Autophagyc Cell Death by the Use of Manganese Doped Zinc Oxide Nanoparticles and Photo-Dynamic Therapy - Peña Luengas, Sandra (2015)
B-Chronic Lymphocytic Leukemia (B-CLL) usually follows an adverse, relentless clinical course by slowly developing drug resistance to fludarabine and other chemotherapeutic agents, as well as by acquiring new different genetic abnormalities. As B-CLL cells spontaneously produce high amounts of Reactive Oxygen Species (ROS) having an altered redox state in relation to that of normal B lymphocytes, we decided to probe different metal Zinc nanoparticles (ZnNPs) and quantify the levels of Singlet Oxigen (SO) to see if variations of its intracellular concentrations could execute and accelerate deadly programs in leukemic cells rather than in normal B lymphocytes, when applied with Photodynamic Therapy (PDT). In this way, we developed and tested a variety of metal ZnNPs of which one made of 0.5% Manganese Doped Zinc Oxide (ZnO:Mn) was finally selected for further testing as it had the best fludarabine resistant B-CLL cells in vitro killing activity, specially when combined with PDT. An interesting and rapidly dying process of B-CLL cells, known as autophagy, was always seen under Transmission Electronic Microscopy (TEM) when incubated with these 0.5% Mn doped ZnO NPs. This phenomenon correlated well with those intracellular increases of SO when PDT was administered, and measured by a novel method first described by us. As this therapy seems to be very specific to fludarabine resistant B-CLL cells, producing almost no damage to normal lymphocytes, it could surely contribute in the near future as a new innovative targeted strategy to be delivered in the clinical setting for the definitive benefit of these bad prognostic patients.